Thymus zygis, Valuable Antimicrobial (In Vitro and In Situ) and Antibiofilm Agent with Potential Antiproliferative Effects - Vukić, Milena D.; Čmiková, Natália; Hsouna, Anis Ben; Saad, Rania Ben; Garzoli, Stefania; Schwarzová, Marianna; Vuković, Nenad L.; Obradović, Ana D.; Matić, Miloš M.; Waszkiewicz-Robak, Bożena; Kluz, Maciej Ireneusz; Kačániová, Miroslava (Plants (Basel), 2023)
With the growing issues of food spoilage, microbial resistance, and high mortality caused by cancer, the aim of this study was to evaluate T. zygis essential oil (TZEO) as a potential solution for these challenges. Here, we first performed GC/MS analysis which showed that the tested TZEO belongs to the linalool chemotype since the abundance of linalool was found to be 38.0%. Antioxidant activity assays showed the superiority of TZEO in neutralizing the ABTS radical cation compared to the DPPH radical. The TZEO was able to neutralize 50% of ABTS•+ at the concentration of 53.03 ± 1.34 μg/mL. Antimicrobial assessment performed by employing disc diffusion and minimal inhibitory concentration assays revealed TZEO as a potent antimicrobial agent with the highest inhibition activity towards tested gram-negative strains. The most sensitive on the treatment with TZEO was Enterobacter aerogenes showing an MIC 50 value of 0.147 ± 0.006 mg/mL and a MIC 90 value of 0.158 ± 0.024 mg/mL. Additionally, an in situ analysis showed great effects of TZEO in inhibiting gram-negative E. coli, P. putida, and E. aerogenes growing on bananas and cucumbers. Treatment with the TZEO vapor phase in the concentration of 500 μg/mL was able to reduce the growth of these bacteria on the food models to the extent > 90%, except for E. coli growth on the cucumber, which was reduced to the extent of 83.87 ± 4.76%. Furthermore, a test on the antibiofilm activity of the tested essential oil revealed its biofilm prevention effects against Salmonella enterica which forms biofilms on plastic and stainless-steel surfaces. Performed tests on the TZEO effects towards cell viability showed no effects on the normal MRC-5 cell line. However, the results of MTT assay of TZEO effects on three cancer cell lines (MDA-MB-231, HCT-116, and K562) suggest that TZEO exerted the strongest effects on the inhibition of the viability of MDA-MB-231 cells, especially after long-term treatment in the highest concentration applied with reducing the viability of the cells to 57%. Additionally, results of NBT and Griess assays suggest that TZEO could be a convenient candidate for future testing for developing novel antitumor therapies.